Material Development Promoted By English For Specific Purposes Teacher - Novi Indriyani; Marni Bawawa; Rezky Uspayanti (Technium Social Sciences Journal, 2023)
English has been considered as the most international language used in the world. As the effect of that, English becomes the global language for worldwide communication in which people are required to acquire the language orally or in written. In Indonesia, English is perceived as one of the important subjects that must be tough at any level of education. ESPecially for the university level, English specifies its purposes and develops its concept of teaching under-aimed at bridging students major to their future competences. Therefore, to achieve the goal, the material for ESP is designed properly by the teacher there. This study aims to unlock the principles of developing the material and the procedures on how it is maintained to develop. Depth interview, observation, and document analysis were occupied in order to drag out the answer of statement problems - the result announced that nine principles found inside the material, the task, the topic, and the level of difficulties are the under-development unit, and the procedure covers the evaluation, design, and implementation.